Information kiosk system for Philippine International Convention Center. - Felizardo, Jerick Martin C. (2013)
An information kiosk is deployed in a public venue to give people self service access to products and services. Kiosks are most often deployed in situations where a problem can be solved by giving people access to self-service tools. The Information Kiosk System for Philippine International Convention Center is a system developed aimed to guide and give information about the convention center. It was developed to help the attendants (e.g. employee, visitors and admin) who were considered as the service priority of the system. C# is the primary language used by the proponents to develop the system and mySQL for the database of the system’s records; the proponents used Adobe Flash CS5 for creating animations for the system. The primary objective of the information kiosk system for PICC is to give a better service quality, ease of use and usefulness for convention center.